Imagining futures: A collaborative policy/device design for wearable computing. (March 2017) - Gandy, Maribeth; Baker, Paul M.A.; Zeagler, Clint
Highlights: The potential uses of, and markets for wearable computing devices is expanding rapidly. Such devices can create barriers or opportunities for positive cultural and social impacts. Design integration of accessibility, interoperability, and supportive policy will improve opportunities and usability. Interdisciplinary collaboration in design, research and device development in social, technological and regulatory contexts is needed. We propose the use of futures studies to craft and explore multidisciplinary images of the future. Abstract: The rapidly expanding market for wearable computing devices (wearables), driven by advances in information and communication technologies (ICT), wireless access, and public acceptance of a design aesthetic, is indicative of the near limitless potential for changing the relationship of users to information context(s). As the adoption of wearable devices spreads, there are cultural and social impacts that represent both barriers and opportunities, with subsequent policy ramifications. All too often designers, technologists, and policymakers operate independently developing products that are out of sync, lack interoperability, or are hindered by well meaning, but obstructive policy. This paper proposes a futures-based, iterative policy-informed design framework for developing wearable devices that guides interdisciplinary collaborators early in the process of designing a research & development plan. This approach allows for the development of "images of the future" through which various potential implications and effects of device design in social, technological, and regulatory contexts can be explored.